2021
DOI: 10.7759/cureus.19450
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Ocular Manifestations in Chronic Myeloid Leukaemia

Abstract: Background: Chronic myeloid leukaemia (CML) presenting with only ocular manifestations either at the initial stage of diagnosis or at relapse is uncommon. We report two cases of CML presenting with isolated visual symptoms. Case series: The first case is a 21-year-old healthy gentleman who presented with left eye painless loss of vision for a one-week duration. Visual acuity was 6/60 in the left eye and 6/6 in the right eye. There were scattered retinal haemorrhages in both eyes and a sub-macular bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As the disease progresses to accelerated and blast phase symptoms, such as headaches, bone pain, joint pain, and lymphadenopathy are more common [ 4 ]. Ocular manifestations in initial phases are usually rare and have been described through only few case reports over time [ 5 , 6 ]. Similar retinal findings can be found in other retinopathies and hence might be missed initially, especially if the patient has other systemic disorders [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the disease progresses to accelerated and blast phase symptoms, such as headaches, bone pain, joint pain, and lymphadenopathy are more common [ 4 ]. Ocular manifestations in initial phases are usually rare and have been described through only few case reports over time [ 5 , 6 ]. Similar retinal findings can be found in other retinopathies and hence might be missed initially, especially if the patient has other systemic disorders [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ophthalmic presentation of CML is a rare event. A recent literature review found 40 published cases in the preceding 49 years 1 and at least seven further cases have subsequently been reported 2–6 . The median WBC count amongst patients with ophthalmologic involvement was 249 × 10 9 /L (range 50–688 × 10 9 /L).…”
mentioning
confidence: 99%
“…A recent literature review found 40 published cases in the preceding 49 years 1 and at least seven further cases have subsequently been reported. [2][3][4][5][6] The median WBC count amongst patients with ophthalmologic involvement was 249 Â 10 9 /L (range 50-688 Â 10 9 /L). There was a male preponderance with an age range of 9-68 years (median 35 years).…”
mentioning
confidence: 99%